Postbiotics Applications as Infectious Disease Control Agent in Aquaculture - Chun, Yao Ang; Motohiko Sanom; Shigeki Dan; Montira Leelakriangsak; Tamrin Mohammad Lal (2020)
Aquaculture is developing so fast that infectious disease outbreak happens regularly. Antibiotic treatment results in development of antibiotic resistance pathogens, thus cause urgent action in searching of other alternative treatment method. Postbiotic was one of the explored strategies among various proposed alternatives. Due to its benefits in agriculture industry, it may be useful in aquaculture industry. Although many reviews were reported on other alternative strategies, the review on postbiotic in aquaculture is limited. This mini review provides an overview of different postbiotics as aquaculture disease control agents. Peptides and exopolysaccharides have antimicrobial properties against bacterial pathogens. Then, short chain fatty acids have both antimicrobial activities against bacterial pathogens and immunostimulating effects to aquatic organism. Vitamins, peptidoglycan and lipopolysaccharide are reported as immunostimulants. Finally, cell surface proteins and teichoic acid can act as vaccine.